2022
DOI: 10.3390/mi13020281
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Cracking Failure in Microbump Joints for 3D Chip-on-Chip Interconnections under Drop Impact

Abstract: With the rapid development of microelectronics packaging and integration, the failure risk of micro-solder joints in packaging structure caused by impact load has been increasingly concerning. However, the failure mechanism and reliability performance of a Cu-pillar-based microbump joint can use little of the existing research on board-level solder joints as reference, due to the downscaling and joint structure evolution. In this study, to investigate the cracking behavior of microbump joints targeted at chip-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…These numerical approaches most commonly use equivalent stresses and plastic strains as indicators of high-risk failure areas (Yang and Meguid, 2013; Gharaibeh et al , 2019). The introduction of linear fracture mechanics in numerical drop test models is considered a more reliable approach for estimating the mechanical response of electronic microcomponents during the drop test (Liu et al , 2022). However, the elastoplastic behaviour of solder bumps makes the use of linear fracture mechanics inaccurate, and the introduction of non-linear fracture mechanics becomes essential.…”
Section: Introductionmentioning
confidence: 99%
“…These numerical approaches most commonly use equivalent stresses and plastic strains as indicators of high-risk failure areas (Yang and Meguid, 2013; Gharaibeh et al , 2019). The introduction of linear fracture mechanics in numerical drop test models is considered a more reliable approach for estimating the mechanical response of electronic microcomponents during the drop test (Liu et al , 2022). However, the elastoplastic behaviour of solder bumps makes the use of linear fracture mechanics inaccurate, and the introduction of non-linear fracture mechanics becomes essential.…”
Section: Introductionmentioning
confidence: 99%
“…They found that cracks not only occur at the interface between the solder and the land but also on the solder and the land itself. Zhen Liu et al studied the crack behavior of chip on chip (COC) stacked interconnection microbump joint under drop impact load [4]. It was found that the crack leading to microbump failure first began at the interface between the IMC layer and solder.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, package-level system-on-packaging can integrate optics, wireless communication, and power module along with MEMS and IC on a common package. For the packaging and integration explained earlier, interconnection techniques have been important as the packaging size determines the cost of the final product [ 20 , 21 , 22 ]. Interconnect techniques frequently used for MCM packaging are wire-bonding, solder balls, metal stud bumps, and ACF (Anisotropic Conductive Film).…”
mentioning
confidence: 99%